Facial symmetry evaluation after experimentally displaced condylar process fracture in methotrexate treated rats - Cavalcanti,Samantha Cristine Santos Xisto Braga (2012)
PURPOSE: To investigate the facial symmetry of high and low dose methotrexate (MTX) treated rats submitted to experimentally displaced mandibular condyle fracture through the recording of cephalometric measurements. METHODS: One hundred male Wistar rats underwent surgery using an experimental model of right condylar fracture. Animals were divided into four groups: A - saline solution (1mL/week); B - dexamethasone (DEX) (0,15mg/Kg); C - MTX low dose (3 mg/Kg/week); D - MTX high dose (30 mg/Kg). Animals were sacrificed at 1, 7, 15, 30 and 90 days postoperatively (n=5). Body weight was recorded. Specimens were submitted to axial radiographic incidence, and cephalometric mensurations were made using a computer system. Linear measurements of skull and mandible, as well as angular measurements of mandibular deviation were taken. Data were subjected to statistical analyses among the groups, periods of sacrifice and between the sides in each group (α=0.05). RESULTS: Animals regained body weight over time, except in group D. There was reduction in the mandibular length and also changes in the maxilla as well as progressive deviation in the mandible in relation to the skull basis in group D. CONCLUSION: Treatment with high dose methotrexate had deleterious effect on facial symmetry of rats submitted to experimentally displaced condylar process fracture.